Current advances in the imaging of atherosclerotic vulnerable plaque using nanoparticles. (March 2022) - Zhang, Ming; Xie, Zhongjian; Long, Haijiao; Ren, Kun; Hou, Lianjie; Wang, Yu; Xu, Xiaodan; Lei, Weixing; Yang, Zhicheng; Ahmed, Shakeel; Zhang, Han; Zhao, Guojun
Abstract: Vulnerable atherosclerotic plaques of the artery wall that pose a significant risk of cardio-cerebral vascular accidents remain the global leading cause of morbidity and mortality. Thus, early delineation of vulnerable atherosclerotic plaques is of clinical importance for prevention and treatment. The currently available imaging technologies mainly focus on the structural assessment of the vascular wall. Unfortunately, several disadvantages in these strategies limit the improvement in imaging effect. Nanoparticle technology is a novel diagnostic strategy for targeting and imaging pathological biomarkers. New functionalized nanoparticles that detect hallmarks of vulnerable plaques are promising for advance further control of this critical illness. The review aims to address the current opportunities and challenges for the use of nanoparticle technology in imagining vulnerable plaques. Graphical abstract: Schematic representation of nanoparticle technology in the imaging of vulnerable atherosclerotic plaque. Image 1